Evaluation of basidiocarps of wood decay mushrooms Ganoderma sp. with FTIR ATR spectroscopy - Bleha, Roman; Skrynnikova, Anastasia; Jablonsky, Ivan; Sinica, Andrej (Problems of Environmental Biotechnology, 2021)
This work is devoted to the evaluation and characterization of Ganoderma basidiocarps with the combination of ATR-FTIR spectroscopy and statistical discrimination methods like PCA or HCA. Obtained results confirmed significant differences in the composition of bases, stems, and pilei of various Ganoderma species at different stages of development. This analytical approach can be used for effective screening of Ganoderma basidiocarps according to their composition.